Keseimbangan kehidupan kerja pada pekerja blue collar: Peran keterlibatan karyawan dan burnout - Wardani, Laila Meiliyandrie Indah; Firmansyah, Rahmat (Konsorsium Psikologi Ilmiah Nusantara, 2019)
The purpose of this study was to determine the effect of employee engagement and burnout on the perception of work-life balance, particularly on blue-collar workers. The study sample comprised of 91 employees of the production section (blue-collar workers) in a multinational company in Jababeka-Cikarang. Sampling was carried out using a stratified technique of proportional approach. The instruments used in this study are The Utrecht Work Engagement Scale (UWES), Maslach Burnout Inventory (MBI-GS), and Work-Life Balance Scale. The study used primary data collection through survey method and secondary data from the company for analysis. Multiple regression analysis showed that employee engagement and burnout influence participants’ perceptions on work-life balance. The result indicates that employee engagement and burnout explained 17.6 percent on the variability of participants’ perceived work-life balance.